PENGARUH KOMUNIKASI INTERNAL, BUDAYA ORGANISASI, DAN PERILAKU KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT DATANG DSSP POWER INDONESIA (The Effect of Internal Communication, Organizational Culture, and Leadership Behavior on Employee Performance of PT Datang DSSP Power Indonesia) - Muhamad Iqbal; Ansir Ansir; La Ode Bahana Adam (Pascasarjana Universitas Halu Oleo, 2021)
The aims of this study were to determine and analyze: (1) The effect of internal communication, organizational culture, and leadership behavior has a significant effect on employee performance of PT Datang DSSP Power Indonesia, (2) The effect of internal communication has a significant effect on employee performance, (3) The effect of organizational culture has a significant effect on employee performance of PT Datang DSSP Power Indonesia of PT Datang DSSP Power Indonesia, (4) The effect of leadership behavior has a significant effect on employee performance of PT Datang DSSP Power Indonesia. The population in this study was all employees of PT Datang DSSP Power Indonesia about 183 employees. The number of samples in this study was taken by using the slovin formula and the sample number of about 65 respondents with probability random sampling technique. The analysis technique was using multiple regression analysis with SPSS 25. The results showed that: (1) Internal communication, organizational culture, and leadership behavior has a positive and significant effect on employee performance of PT Datang DSSP Power Indonesia, (2) Internal communication has a positive and significant effect on employee performance, (3) Organizational culture has a positive and significant effect on employee performance, (4) Leadership behavior has a positive and significant effect on employee performance of PT Datang DSSP Power Indonesia.